211 - SOCIOECONOMIC PROFILE OF CHILDREN UNDER FIVE YEARS OLD HOSPITALIZED FOR ACUTE RESPIRATORY (Fiep Bulletin - online, 2011)
Identify the socioeconomic profile of children under five years old hospitalized for acute respiratory illness at University Hospital Pequeno Anjo, Itajaí, Santa Catarina. The study was conducted through questionnaires of closed questions to parents and / or caregivers of hospitalized children. There was a male predominance with 68% of the sample was composed of 54% of children aged 1 year and 1 month to 3 years, where the pneumonia, occurred in 80% of cases, 30% of mothers had not completed elementary school. Income in 53% of households ranged from 1 to 3 minimum wages. Of all the male children 34% were age 1 year and 1 month to 3 years, 50% were hospitalized with pneumonia and 32% had been breastfed for less than a month. The socioeconomic profile was found the majority of mothers with low education levels, with primary school aged greater than or equal to 20 years who become pregnant for 37 weeks or more and who did not smoke, low income families, with children in mostly boys, aged 1 year and 1 day to 3 years, hospitalized for pneumonia and fed to a month of life. It is hoped that this study can contribute to reducing morbidity and mortality, from the identification of predisposing factors for acute respiratory diseases.
Keywords: socioeconomic; less than five years; acute respiratory diseases